2022
DOI: 10.18046/j.estger.2022.164.4996
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre el género del director ejecutivo y la aplicación de la responsabilidad social empresarial

Abstract: En este documento se aborda el problema de la posible influencia del género del director ejecutivo sobre la incorporación de la responsabilidad social empresarial. El objetivo fue estudiar si existe relación entre estas variables. Se utilizó una metodología de tipo cuantitativo, aplicada a una base de datos con información sobre el uso de prácticas generales de gestión. Se trata de una base de 107 prácticas específicas de la responsabilidad social empresarial. Para estudiar la relación entre el género del dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In his opinion, these managers enhance the presence of other factors also associated with CSR, such as the integration of women on the boards and the existence of external directors. [20] found that companies with a CSR manager perform better in the application of CSR, but that the difference was not statistically significant, most likely because of the small sample used in their research.…”
Section: Csr Managers and Csr Implementationmentioning
confidence: 90%
See 1 more Smart Citation
“…In his opinion, these managers enhance the presence of other factors also associated with CSR, such as the integration of women on the boards and the existence of external directors. [20] found that companies with a CSR manager perform better in the application of CSR, but that the difference was not statistically significant, most likely because of the small sample used in their research.…”
Section: Csr Managers and Csr Implementationmentioning
confidence: 90%
“…Accordingly, they proposed that "the person responsible for CSR, whatever the name given in each company [...] is undoubtedly faced with the difficult task of introducing this criterion into the daily management of the company" [19] (p. 3). For [20], the incorporation of CSR creates the need for an internal leadership, which for different reasons does not usually fall on the classic functional managers, and this is the reason why many companies have created specific CSR managers. Argandoña et al (2008) [19] found that in Spain, this function is given different names (such as "CSR director", "CSR manager", and "CSR coordinator"), which in turn indicates that it can be located at different hierarchical levels.…”
Section: Csr Managers and Csr Implementationmentioning
confidence: 99%